Pengaruh E-Learning dan Media Sosial Terhadap Motivasi Belajar Mahasiswa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung - Habibillah, Putri; Zaini, Muhamad; Ngadhimah, Mambaul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The objectives of this research to explain the effect of (1) E-Learning on the learning motivation; (2) Social Media as a learning medium on the learning motivation; (3) E-Learning and social media as a learning medium on the learning motivation. This research uses a quantitative approach with correlational research type. The data analysis technique used simple and multiple linier regression test. The results of this research indicatet that (1) there is a positive and significant influence between E-Learning on the learning motivation on a simple linier regression test from tcount>ttable (7.295 > 1.97) and a significance value of 0.000 < 0.05; (2) there is a positive and significant influence between social media as a learning medium on the learning motivation on a simple linier regression test from tcount>ttable (7.476 > 1.97) and significance value of 0.000 < 0.05; (3) there is a positive and significant influence between E-Learning and social media as learning media on learning motivation on the calculation of multiple linier regression test from Fcount>Ftable (34.831 > 3.04) and a significance valu of 0.000 < 0.05.